Akuntansi masjid: Laporan keuangan pembangunan Masjid Agung Jami’ Kota Malang - Nasikhah, Mazroatun (Maliki Interdisciplinary Journal, 2024)
Recording in the mosque accounting report, in which only the mosque receives and expenses, both in development activities and in daily activities, and errors in the activity of the report do not include the number of assets owned by the mosque so that there are often cases of loss of mosque assets due to the weak financial reporting system.